Variables associated with environmental scanning among clinicians at substance abuse treatment clinics - Alison L. Koch; Cynthia L. Arfken; Marcus W. Dickson; Elizabeth Agius; & Jacqueline K. Mitchelson (Information Research: An International Electronic Journal)
Introduction. Environmental scanning, as a component of absorptive capacity, has been shown to be associated with increased use of innovative treatment techniques at substance abuse treatment programmes. As the transfer of innovative, evidence-based treatment techniques from research to practice is gaining attention, we aimed to identify variables associated with higher levels of environmental scanning among substance abuse treatment clinicians. Method. A cross-sectional survey was administered to 162 clinicians at 15 substance abuse treatment clinics in Michigan. Measures: Environmental scanning was measured by frequency of use of the Internet, journals, seminars or conferences, and people at other treatment clinics for new substance abuse treatment information. Clinicians were asked for their perceptions of their clinic’s openness to new treatment techniques and support for acquiring new information, access to and satisfaction with information sources at work, as well as if they feel it is their job to keep up to date with current treatment research. Additional measures included whether they intended to quit their jobs and whether they were emotionally drained from work. Findings: We found positive associations between environmental scanning and perceived clinic support for acquiring new information, perceived clinic openness to new treatment techniques, access to e-mail and Internet at work, and satisfaction with resources. Turnover intention and being emotionally drained were negatively associated with environmental scanning. Conclusion. : Individual and organizational level variables were found to be associated with higher levels of environmental scanning activity. Although the causal directions of these associations are not known, the findings suggest ways to increase environmental scanning among clinicians.